“Recursos didácticos digitales para la enseñanza y aprendizaje en la asignatura de ciencias naturales, en el sexto año de educación general básica, en la Unidad Educativa “Ana Páez” en el período 2020 - 2021” - Polo Mejia, Jennifer Tatiana (2021)
Now, educative process and constantly evolution of technology requires that education must be related to digital applications, because they allow an interactive learning between teacher and student. In this way, teacher must assume the responsibility to implement innovative resources, strategies and activities at teaching and learning process. However, today teachers choose to use school textbook as their only one didactic resource, which leads to the so-called textcentrism, that is, the absence of activities and tasks on teaching and learning process, which results in a class improvisation. The objective of this research was to design digital resources through Powtoon tool to strengthen teaching and learning process of Natural Sciences subject at “Ana Paez” Educative Unit. The used methodology was qualitative research based on next stages: preparatory, field, analytical and dissemination. The applied method was theoretical inductive and empirical through observation and interview techniques that allowed to interpret, explain, and explore relevant aspects of digital didactic resources for teaching and learning of Natural Sciences. The result of the proposal is the publication of ten educational videos on YouTube, in order to promote autonomous learning through technological tools use to strengthen training process in Natural Sciences subject. As such, this research project contributes to innovation processes in the classroom through technology incorporation as a tool in teaching and learning process.